Self-determination theory and its implications for team motivation - Grenier, S.; Gagné, Marylene; O'Neill, T. (2024)
Despite decades of research on teams, there are still gaps in our understanding of motivational dynamics within teams and the emergence of team-level motivation. We advance a new team motivation model that invokes self-determination theory (SDT), multilevel theory, emergence processes, and identity construction. Using the conceptualization of motivation offered by SDT, we define team motivation as a collective source of energy driving the direction, intensity, and persistence of team activities. By using SDT to develop the process-based team motivation emergence model, we describe the role of human psychological needs that are involved in the emergence of this collective construct. An interpersonal feedback loop intertwined with a team process feedback loop predict how team members' individual motivations converge and then transform into team-level motivation through a process of identity construction. Propositions for testing the model are advanced, as well as suggestions for methodological and analytical considerations.